School Principals’ Leadership in Building School Community Partnerships: A Multisite Study to Enhance Educational Quality at SDN Tempuran I and SDN Tempuran II Pasrepan - Arif, Syamsul; Thohirin, Ahmad; Faizin, A.; Rimadani, Eprilia (The Future of Education Journal, 2026)
This study examines the role of school principals’ leadership in building partnerships between schools and the community to enhance educational quality at SDN Tempuran I and SDN Tempuran II. A qualitative approach with a multisite case study design was employed to understand the meaning and practices of leadership within the real context of rural elementary schools. Data were collected through semi-structured interviews, participatory observations, and documentation of partnership activities. The findings reveal that school principals implement collaborative leadership that encourages the involvement of school committees, parents, and community members in decision-making processes and the development of educational programs. These partnerships contribute significantly to improvements in learning facilities, resource support, and more active stakeholder participation in educational activities. The findings underscore the importance of adaptive leadership and effective communication strategies in strengthening school–community relationships in rural settings.